Disruptive Hearing Technologies and Mild Sensorineural Hearing Loss I: Accessibility and Affordability Issues - Jilla, Anna Marie; Johnson, Carole E.; Danhauer, Jeffrey L. (Seminars in Hearing, 2018)
Limited accessibility to and affordability of hearing health care (HHC) and hearing aids (HAs) are two reasons why people do not seek treatment for their hearing losses. This article is the first in a series of two and discusses affordability issues (i.e., billing models, cost-effectiveness, insurance coverage, and reimbursement) related to and provides a historical context for the Over-the-Counter Hearing Aid Act of 2017. This piece of legislation supports development of a new class of over-the-counter HAs that represents a disruptive technology that may transform the HHC industry by reducing costs specific to the device. A discussion of ethical issues and the importance of using evidence-based practice guidelines set the stage for the second article in this series, which reviews relevant research on issues pertaining to persons with mild hearing loss.
Keywords: hearing aids; over-the-counter; direct-to-consumer; hearing loss; adult; insurance; health-related quality of life